Application of melilite structure electro-optical crystal in preparation of photoelectric device

By adjusting the Al/Ga ratio of yellow feldspar structure electro-optical crystal Ca2Al2-xGaxSiO7, combined with lifting method growth technology, the problem of insufficient performance of existing electro-optical crystals is solved, and high resistivity and low cost electro-optical crystal preparation is achieved, suitable for a variety of Manufacturing of optoelectronic devices.

CN119162667APending Publication Date: 2024-12-20SHANDONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411043539.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-31
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In terms of performance, existing electro-optical crystals have problems such as high half-wave voltage, weak photo damage resistance, and unstable physical and chemical performance, and it is difficult to meet the requirements of low half-wave voltage, stability and high optical quality at the same time.

Method used

Using the electro-optical crystal of yellow feldspar structure, Ca2Al2-xGaxSiO7, calcium-aluminum yellow feldspar crystals with different Al/Ga ratios are obtained by adjusting the x value. Combined with lifting growth technology, single-sized with high resistivity, low cost, easy crystallization and large growth sizes are prepared. Crystal, used to prepare optoelectronic devices.

Benefits of technology

It realizes electro-optical crystals of yellow feldspar structure without phase change at room temperature, which are cheap, easy to crystallize and grow large-size, and are used to prepare electro-optical switches, electro-optical modulators and other devices, and are suitable for the field of laser and communication technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162667A_ABST
    Figure CN119162667A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of crystals and devices, and relates to application of an electro-optical crystal with a melilite structure in preparation of a photoelectric device. The chemical formula of the melilite structure electro-optical crystal is Ca2Al2-xGaxSiO7, the melilite structure electro-optical crystal belongs to a # imgabs0 # space group, and x is larger than or equal to 0 and smaller than 2. The CAGS crystal grows by adopting a Czochralski method, and a series of crystals with different ion concentrations are obtained by mixing raw materials in different proportions; the CAGS crystal is used for manufacturing an electro-optical device; the electro-optical device comprises but is not limited to an electro-optical switch, an electro-optical modulator, a scanner and the like. The crystal prepared by the method has the characteristics of no phase change at room temperature, low cost, easiness in crystallization and large growth size.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of crystals and devices, and relates to the application of a chalcedony structure electro-optical crystal in the preparation of optoelectronic devices. Background Art

[0002] The electro-optic effect refers to the phenomenon that the refractive index of a crystal changes under the action of an external electric field. It can be used to control the intensity, phase and propagation direction of light. Various tunable optical communication devices prepared based on the electro-optic effect of electro-optic crystal materials, such as electro-optic switches, electro-optic modulators, scanners, etc., have broad applications and prospects in the fields of laser radar, quantum communication and information processing.

[0003] At present, there are many types of commercial electro-optical crystals. The commonly used electro-optical crystals in the visible band are lithium niobate (LiNbO3), lithium tantalate (LiTaO3), potassium dihydrogen phosphate (KH2PO4), ammonium dihydrogen phosphate (NH4H2PO4), barium metaborate (BaB2O4), etc. Among them, lithium niobate crystals and lithium tantalate crystals have low half-wave voltage and stable physical and chemical properties, but their optical damage threshold is low. Potassium dihydrogen phosphate crystals and ammonium dihydrogen phosphate crystals have high optical quality and optical damage threshold, but their half-wave voltage is high, and water-soluble crystals are easy to deliquesce, and relevant measures to prevent deliquesce are required. In the infrared band, practical electro-optical crystals mainly include semiconductor crystals such as gallium arsenide (GaAs) and cadmium telluride (CdTe). With the wide application of electro-optical crystals in the optical field, higher requirements are put forward for their performance, including low half-wave voltage, strong resistance to light damage, stable physical and chemical properties, and easy to obtain high-quality large-size single crystals. However, there is a lack of crystals that meet all the above requirements. In commercial applications, it is necessary to select the most suitable crystals according to actual requirements. Therefore, it is a hot topic in the current field of electro-optical crystals to explore a crystal that has low half-wave voltage, stable physical and chemical properties, high optical quality and optical damage threshold, which is of great significance. Summary of the invention

[0004] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide an application of a pyroxene structured electro-optical crystal in the preparation of optoelectronic devices. The electro-optical crystal used in the present invention has the advantages of no phase change at room temperature, low cost, easy crystallization and large size growth.

[0005] In order to achieve the above object, the technical solution of the present invention is:

[0006] In one aspect, a chalcite structure electro-optical crystal is used in the preparation of an optoelectronic device, wherein the chemical formula of the chalcite structure electro-optical crystal is: Ca2Al 2-x Ga x SiO7, belongs to Space group, 0≤x<2.

[0007] When x=0, the chemical formula is: Ca2Al2SiO7, referred to as CAS. When x≠0, referred to as CAGS.

[0008] When x = 0.17, the unit cell parameters of the CAGS crystal are The piezoelectric constant is d 14 =10.52pC / N,d 36 is 3.24pC / N; the c-axis high temperature resistivity ρ at 600℃, 700℃, and 800℃ is 2.3×10 9 Ω·cm、3.7×10 8 Ω·cm、8.1×10 7 Ω·cm. When x=1.6, its unit cell parameters are

[0009] α=β=γ=90°. The structural characteristics and performance parameters of CAS crystals and CAGS crystals indicate that by changing the x value to obtain different Al / Ga ratios, gallium-doped calcite crystals with different photoelectric properties can be obtained, which can be used to prepare photoelectric devices.

[0010] In some embodiments, the light-transmitting surface of the electro-optical crystal is double-sided polished, and a conductive film is disposed in the direction of applying the electric field. Specifically, the conductive film may be a gold film, a silver film, or a copper film, and the coating method may be ion sputtering, vacuum coating, or the like.

[0011] In some embodiments, the electro-optical crystal is prepared by a Czochralski method.

[0012] Specifically, the steps of the Czochralski method are as follows:

[0013] According to the stoichiometric ratio of Ca2Al2SiO7 crystals and Ca2Ga2SiO7 crystals, the calcium source, aluminum source, gallium source and silicon source are mixed respectively, pressed and sintered into Ca2Al2SiO7 polycrystalline material and Ca2Ga2SiO7 polycrystalline material, Ca2Al2SiO7 polycrystalline material and Ca2Ga2SiO7 are added in proportion and heated to melt, and after the melt state is stable, the temperature is lowered to the seeding temperature, and the CAS crystal is used as a seed crystal to descend to the melt surface and neck, and then the shoulder is released and the isodiametric growth is carried out, and the growth process is pulled. Further, the sintering temperature is 1200-1400°C. Further, the melting temperature is 1500-1700°C. Further, the melting is carried out under the condition of a nitrogen atmosphere containing oxygen; further, the volume fraction of oxygen is 0.30-0.40%. In order to stabilize the melt state, the melt is overheated by 10-30°C. Furthermore, during the growth process, the rotation speed is 8-20 rpm and the pulling speed is 0.5-5 mm·h -1.

[0014] The calcium source described in the present invention refers to a compound containing calcium, such as calcium carbonate, calcium oxide, etc.

[0015] The aluminum source described in the present invention refers to a compound containing aluminum element, such as aluminum oxide.

[0016] The gallium source described in the present invention refers to a compound containing gallium element, such as gallium trioxide.

[0017] The silicon source described in the present invention refers to a compound containing silicon, such as silicon dioxide.

[0018] In some embodiments, the optoelectronic device includes but is not limited to an electro-optic switch and / or an electro-optic modulator and / or a scanner, etc.

[0019] Specifically, the preparation method of the electro-optical switch is: provide two electro-optical crystals for compensating the natural birefringence of the crystal, the direction of light passing is the physical X direction or Y direction, polish the two crystal planes in the direction of light passing, plate a conductive film on the Z end face of the crystal as an electrode, apply an electric field along the physical Z direction, and prepare the electro-optical switch.

[0020] Specifically, the preparation method of the electro-optic modulator is: polishing the two end faces of the electro-optic crystal in the light transmission direction, applying an electric field parallel to the propagation direction of light and perpendicular to the propagation direction of light according to the requirements of the longitudinal modulation mechanism or the transverse modulation mechanism for the electric field direction, and preparing the electro-optic modulator.

[0021] On the other hand, a method for testing the modulation of the electro-optic effect of a chalcite structure electro-optic crystal includes testing the modulation of the longitudinal electro-optic effect and / or testing the modulation of the transverse electro-optic effect; the chemical formula of the chalcite structure electro-optic crystal is: Ca2Al 2-x Ga x SiO7, belongs to Space group, 0≤x<2.

[0022] The longitudinal electro-optic effect refers to the electro-optic effect produced when the direction of the electric field applied to the crystal is parallel to the direction of light propagation in the crystal; the transverse electro-optic effect refers to the photoelectric effect produced when the direction of the electric field applied to the crystal is perpendicular to the direction of light propagation in the crystal.

[0023] Due to the electro-optic effect, after applying a DC voltage to the crystal, the two light waves that come out have a certain phase difference. When the light wave passes through the analyzer, a beam of light is formed whose intensity changes with the DC voltage. As the voltage increases, the phase difference becomes larger and the intensity of the beam decreases. When the phase difference between the two light waves increases to π, the light intensity passing through the analyzer is zero. At this time, the voltage applied is the half-wave voltage. The electro-optic coefficient of the crystal is obtained based on the half-wave voltage.

[0024] In some embodiments, in the test of modulation of the longitudinal electro-optical effect, a polarizer, the electro-optical crystal, an analyzer and a photodetector are arranged in sequence, and the electro-optical crystal is electrically connected to a power source.

[0025] In some embodiments, in the modulation test of the lateral electro-optical effect, a polarizer, a first crystal, a second crystal, an analyzer and a photodetector are arranged in sequence, the first crystal and the second crystal are both the electro-optical crystals, the Z direction of the first crystal and the Z direction of the second crystal are perpendicular, and the Z direction of the first crystal and the Z direction of the second crystal are both perpendicular to the direction of the light beam.

[0026] The beneficial effects of the present invention are:

[0027] The orthoclase structure electro-optical crystal provided by the present invention has the advantages of high resistivity, low cost, easy crystallization and growth of large-size single crystals, and is used to make devices such as electro-optic switches, electro-optic modulators, scanners, etc., and can be applied to technical fields such as lasers and communications. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0029] Figure 1 This is a picture of the CAGS crystal prepared in Example 1 of the present invention;

[0030] Figure 2 The rocking curve of the CAS crystal prepared in Example 1 of the present invention;

[0031] Figure 3 The rocking curve of the CAGS crystal prepared in Example 1 of the present invention;

[0032] Figure 4 is a schematic diagram of the longitudinal modulation mode in Embodiment 3 of the present invention;

[0033] Figure 5 It is a schematic diagram of the transverse modulation mode in Example 3 of the present invention. DETAILED DESCRIPTION

[0034] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.

[0035] Example 1

[0036] The CAGS crystal is grown by the Czochralski method, which includes the following steps:

[0037] According to the stoichiometric ratio of Ca2Al2SiO7 (CAS) and Ca2Ga2SiO7 (CGS), CaCO3, Al2O3, Ga2O3 and SiO2 powders with a purity of 99.99% were weighed respectively, wherein Ga2O3 was weighed in excess of 2wt.% due to its volatile nature. The raw materials were mixed and pressed into blocks, which were sintered at 1400°C and 1200°C for 50 hours respectively to obtain polycrystalline materials of CAS and CGS.

[0038] The above-mentioned CAS and CGS polycrystalline materials were loaded into a crucible at a molar ratio of 9:1. In a nitrogen atmosphere containing 0.36% oxygen, the temperature was raised to about 1600°C for 10 hours to melt the polycrystalline materials by medium frequency induction heating. The temperature was kept constant for 8 hours to stabilize the melt state, and then the temperature was lowered to the seeding temperature. <100> The CAS crystal in the direction of the melt was used as the seed crystal. The seed crystal was lowered to the melt surface and the crystal growth began. During the growth process, the crystal was seeded at a speed of 20 rpm. When the shoulder was put to the required diameter, the speed was evenly reduced to 15 rpm and the speed was 1.5 mm·h -1 The pulling speed is set at 50 mm, and the pulling is stopped when the diameter grows to 50 mm.

[0039] The grown crystals were pulled out of the melt surface and then cooled to room temperature at a rate of 30°C / h to obtain Ca2Al 1.83 Ga 0.17 SiO7 crystal.

[0040] The unit cell parameters of the obtained crystal are: The obtained crystals have the same crystal structure as that of gehlenite crystals.

[0041] Figure 1 This is a picture of the CAGS crystal grown in this example. As can be seen from the picture, the crystal has a complete, transparent appearance and no bubbles.

[0042] Figures 2-3 4 and 4 are rocking curves of the CAS crystal and the CAGS crystal grown in this embodiment. It can be seen from the figure that the obtained CAGS crystal has good crystal quality compared with the CAS crystal and is superior to the CAS crystal.

[0043] Example 2

[0044] The CAGS crystal is grown by the Czochralski method, which includes the following steps:

[0045] According to the stoichiometric ratio of Ca2Al2SiO7 (CAS) and Ca2Ga2SiO7 (CGS), CaCO3, Al2O3, Ga2O3 and SiO2 powders with a purity of 99.99% were weighed respectively, wherein Ga2O3 was weighed in excess of 2wt.% due to its volatile nature. The raw materials were mixed and pressed into blocks, which were sintered at 1400°C and 1200°C for 50 hours respectively to obtain polycrystalline materials of CAS and CGS.

[0046] The above-mentioned CAS and CGS polycrystalline materials were loaded into a crucible at a molar ratio of 1:1. In a nitrogen atmosphere containing 0.36% oxygen, the polycrystalline materials were melted by medium frequency induction heating after 10 hours at a temperature of about 1600°C. The temperature was kept constant for 8 hours to stabilize the melt state, and then the temperature was cooled to the seeding temperature. <100> The CAS crystal in the direction of the melt was used as the seed crystal. The seed crystal was lowered to the melt surface and the crystal growth began. During the growth process, the crystal was seeded at a speed of 20 rpm. When the shoulder was put to the required diameter, the speed was evenly reduced to 15 rpm and the speed was 1.5 mm·h -1 The pulling speed is set at 50 mm, and the pulling is stopped when the diameter grows to 50 mm.

[0047] The grown crystals were pulled out of the melt surface and then cooled to room temperature at a rate of 30°C / h to obtain Ca2Al 1.02 Ga 0.98 SiO7 crystal.

[0048] The obtained crystals had the crystal structure described in Example 1.

[0049] Example 3

[0050] The CAGS crystal is grown by the Czochralski method, which includes the following steps:

[0051] According to the stoichiometric ratio of Ca2Al2SiO7 (CAS) and Ca2Ga2SiO7 (CGS), CaCO3, Al2O3, Ga2O3 and SiO2 powders with a purity of 99.99% were weighed respectively, wherein Ga2O3 was weighed in excess of 2wt.% due to its volatile nature. The raw materials were mixed and pressed into blocks, which were sintered at 1400°C and 1200°C for 50 hours respectively to obtain polycrystalline materials of CAS and CGS.

[0052] The above-mentioned CAS and CGS polycrystalline materials were loaded into a crucible at a molar ratio of 0.95:0.05, and in a nitrogen atmosphere containing 0.36% oxygen, the temperature was raised to about 1600°C for 10 hours to melt the polycrystalline materials, and the temperature was kept constant for 8 hours to stabilize the melt state, and then the temperature was lowered to the seeding temperature, and the polycrystalline materials were heated to 1600°C for 10 hours to melt the polycrystalline materials. <100> The CAS crystal in the direction of the melt was used as the seed crystal. The seed crystal was lowered to the melt surface and the crystal growth began. During the growth process, the crystal was seeded at a speed of 20 rpm. When the shoulder was put to the required diameter, the speed was evenly reduced to 15 rpm and the speed was 1.5 mm·h -1 The pulling speed is set at 50 mm, and the pulling is stopped when the diameter grows to 50 mm.

[0053] The grown crystals were pulled out of the melt surface and then cooled to room temperature at a rate of 30°C / h to obtain Ca2Al 1.92 Ga 0.08 SiO7 crystal.

[0054] The obtained crystals had the crystal structure described in Example 1.

[0055] Example 4

[0056] The method for testing the electro-optical performance of a CAGS crystal comprises the following steps:

[0057] Figure 4 The figure shows the principle diagram of the longitudinal modulation mode. The test device is built according to the principle diagram, the two crystal surfaces through which light passes are polished, an electric field of a certain intensity is applied to the crystal along the direction of light transmission, and the extinction condition is detected.

[0058] Figure 5 The figure shows the principle diagram of the lateral modulation mode. The test device is built according to the principle diagram, the two crystal surfaces through which light passes are polished, and an electric field of a certain intensity is applied to the side of the crystal perpendicular to the light transmission direction to detect the extinction condition.

[0059] Due to the electro-optical effect of the crystal, when a DC voltage is applied to it, two light waves will come out and produce a certain phase difference. When the two light waves pass through the analyzer, due to polarization interference, a beam of light whose intensity changes with the DC voltage is formed. As the applied voltage increases, the phase difference increases and the intensity of the beam decreases. When the phase difference between the two light waves increases to π, the light intensity passing through the analyzer is zero. At this time, the voltage applied is the half-wave voltage, and the electro-optic coefficient of the crystal is calculated based on the half-wave voltage.

[0060] Example 5

[0061] Making a CAGS electro-optical switch

[0062] First, place the CAGS crystal along <100> The crystal direction is processed into two cubic crystals of the same size, and the remaining four crystal faces are respectively along <010> and <001> Direction, the size of the two crystals is 6×6×20mm 3 ,in <010> and <001> The width in both directions is 6mm. <100> The length of the two crystals is 20 mm, and they are respectively called crystal A and crystal B. <100> Place the two crystal faces in parallel and place the crystal A <010> The direction is similar to that of crystal B. <001> Direction is parallel, the light transmission direction of the crystal is <100> Direction. <100> The crystal planes in the direction are polished. <001> The crystal planes in the two directions are coated to serve as conductive electrodes. The coating thickness is determined to achieve conductivity. Voltage is applied along the coated crystal planes of the two crystals to prepare an electro-optical switch, which can be used in lasers.

[0063] Example 6

[0064] Making an Electro-Optic Modulator

[0065] Place the CAGS crystal along <100> Direction processing into a regular cubic crystal, so that its four sides are <010> Direction and <001> Direction, crystal size is 6×6×20mm 3 , the light transmission direction of the crystal is <100> Direction. Place the crystal <100> According to the requirements of the longitudinal modulation mechanism or the transverse modulation mechanism for the direction of the applied electric field, an electric field of a certain intensity is applied parallel to the propagation direction of light and perpendicular to the propagation direction of light to prepare an electro-optical modulator.

[0066] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. Application of a chalcite structure electro-optical crystal in the preparation of an optoelectronic device, wherein the chemical formula of the chalcite structure electro-optical crystal is: Ca2Al 2-x Ga x SiO7, belongs to Space group, 0≤x<2.

2. The use of the chalcedony structure electro-optical crystal according to claim 1 in the preparation of optoelectronic devices, characterized in that: The light-transmitting surface of the electro-optical crystal is double-sided polished, and a conductive film is provided in the direction of applying the electric field; or, the conductive film is a gold film, a silver film or a copper film, or, the coating method is ion sputtering or vacuum coating.

3. The use of the chalcedony structure electro-optical crystal according to claim 1 in the preparation of optoelectronic devices, characterized in that: The preparation method of the electro-optical crystal is a Czochralski method.

4. The use of the chalcedony structure electro-optical crystal according to claim 1 in the preparation of optoelectronic devices, characterized in that: The steps of the Czochralski method are as follows: According to the stoichiometric ratio of Ca2Al2SiO7 crystal and Ca2Ga2SiO7 crystal, calcium source, aluminum source, gallium source and silicon source are mixed respectively, pressed and sintered into Ca2Al2SiO7 polycrystalline material and Ca2Ga2SiO7 polycrystalline material, Ca2Al2SiO7 polycrystalline material and Ca2Ga2SiO7 are added in proportion and heated to melt, after the melt state is stable, the temperature is lowered to the seeding temperature, CAS crystal is used as a seed crystal to descend to the melt surface and neck, then shoulders are released and isodiametric growth is carried out, and pulling is carried out during the growth process; or, the sintering temperature is 1200-1400°C; or, the melting temperature is 1500-1700°C; or, the melting is carried out under nitrogen atmosphere containing oxygen; or, the volume fraction of oxygen is 0.30-0.40%; or, during the growth process, the rotation speed is 8-20rpm and the pulling speed is 0.5-5mm·h -1 .

5. The use of the chalcedony structure electro-optical crystal according to claim 1 in the preparation of optoelectronic devices, characterized in that: The optoelectronic devices include, but are not limited to, electro-optic switches and / or electro-optic modulators and / or scanners.

6. The use of the chalcedony structure electro-optical crystal according to claim 1 in the preparation of optoelectronic devices, characterized in that: The preparation method of the electro-optical switch is as follows: two electro-optical crystals are provided to compensate for the natural birefringence of the crystals, the light passing direction is the physical X direction or Y direction, the two crystal faces in the light passing direction are polished, a conductive film is plated on the Z end face of the crystal as an electrode, an electric field is applied along the physical Z direction, and the electro-optical switch is prepared.

7. The use of the chalcedony structure electro-optical crystal according to claim 1 in the preparation of optoelectronic devices, characterized in that: The preparation method of the electro-optic modulator is: polishing the two end faces of the electro-optic crystal in the light transmission direction, applying an electric field parallel to the propagation direction of light and perpendicular to the propagation direction of light according to the requirements of the longitudinal modulation mechanism or the transverse modulation mechanism for the electric field direction, and preparing the electro-optic modulator.

8. A method for testing the modulation of the electro-optical effect of a chalcedony structure electro-optical crystal, characterized in that: Including the test of modulation of longitudinal electro-optical effect and / or the test of modulation of transverse electro-optical effect; The chemical formula of the pyroxene structure electro-optical crystal is: Ca2Al 2-x Ga x SiO7, belongs to Space group, 0≤x<2.

9. The method for testing the modulation of the electro-optical effect of the chalcedony structure electro-optical crystal according to claim 8, characterized in that: In the modulation test of the longitudinal electro-optical effect, a polarizer, the electro-optical crystal, an analyzer and a photodetector are arranged in sequence, and the electro-optical crystal is electrically connected to a power supply.

10. The method for testing the modulation of the electro-optical effect of the chalcedony structure electro-optical crystal according to claim 8, characterized in that: In the modulation test of the transverse electro-optical effect, a polarizer, a first crystal, a second crystal, an analyzer and a photodetector are arranged in sequence, the first crystal and the second crystal are both electro-optical crystals, the Z direction of the first crystal and the Z direction of the second crystal are perpendicular, and the Z direction of the first crystal and the Z direction of the second crystal are both perpendicular to the direction of the light beam.